Development of 3D-Printed Orthopedic Insoles for Patients with Diabetes and Evaluation with Electronic Pressure Sensors - Zuñiga, Juan (2022)
“The correct distribution of loads on foot, known as plantar pressures, is a relevant parameter for evaluating the evolution of some diseases. Anomalies can lead to pain and discomfort in other body parts. Diabetes changes foot tissues and compromises biomechanics, resulting in ulcers and, eventually, amputation. Customized insoles allow the redistribution of plantar pressures and are a complementary strategy to diabetes management. Nowadays, scanning and 3D printing technology can generate faster and more accurate customized insoles opening new opportunities for local medical device development. This study reports the development of 3D-printed insoles using two polymers, thermoplastic polyether-polyurethane and thermoplastic polyurethane polyester-based polymer, and the evaluation of plantar pressure distribution in walk trials using a clinical protocol and low-cost electronic system. The two 3D-printed insoles performed as well as a standard insole. No significant difference was found in average peak pressure distribution. The digital manufacturing workflow of customized insoles can be implemented in middle-income countries. Three-dimensionally printed insoles have the potential for diabetes management, and further material evaluations are needed before using them in health facilities.“